2020
DOI: 10.7570/jomes20028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence and Mechanisms of High-Protein Diet-Induced Weight Loss

Abstract: Several clinical trials have found that consuming more protein than the recommended dietary allowance not only reduces body weight (BW), but also enhances body composition by decreasing fat mass while preserving fat-free mass (FFM) in both low-calorie and standard-calorie diets. Fairly long-term clinical trials of 6-12 months reported that a high-protein diet (HPD) provides weight-loss effects and can prevent weight regain after weight loss. HPD has not been reported to have adverse effects on health in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 46 publications
4
74
2
6
Order By: Relevance
“…Several studies have evaluated the effects of a high-protein diet. One study [29] reported that a high-protein diet (1.07-1.60 g/kg body weight/day) lasting for 6-12 months was an effective and safe way to reduce weight: the high protein produced satiety and increased energy expenditure. Furthermore, high-protein diets lasting for 12 weeks could signi cantly improve body composition in women with normal-weight obesity, reducing the waist circumference, fat mass, and body fat percentage and increasing lean body mass [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the effects of a high-protein diet. One study [29] reported that a high-protein diet (1.07-1.60 g/kg body weight/day) lasting for 6-12 months was an effective and safe way to reduce weight: the high protein produced satiety and increased energy expenditure. Furthermore, high-protein diets lasting for 12 weeks could signi cantly improve body composition in women with normal-weight obesity, reducing the waist circumference, fat mass, and body fat percentage and increasing lean body mass [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our study presents several limitations. First, we excluded patients with renal and hepatic diseases, and therefore the safety of a high-protein diet for these patients must be assessed because of its potential effects on renal function [29,35]. Second, although we asked patients to fast for 6-8 hours before blood collection, some patients, especially at outpatients visit, may have failed to follow it, which would affect our laboratory test results.…”
Section: Discussionmentioning
confidence: 99%
“…High-protein diets, in which protein intake is increased by 25% of energy, can be effective for weight loss and weight maintenance. 27,28 In a study of Korean Despite the controversies discussed above, low-fat diets are still effective for weight management in Korea. However, the quality of carbohydrates in low-fat diets should be emphasized.…”
Section: What Is Next After the Low-carb Diet Trend In Korea?mentioning
confidence: 99%
“…Еще одно предполагаемое достоинство высокобелкового рациона -более раннее и продолжительное насыщение по сравнению с другими диетами, что не только способствует снижению массы тела, но и делает его комфортным для человека [19]. На основе визуальной аналоговой шкалы (ВАШ), которая является стандартным инструментом для измерения субъективного чувства голода и насыщения, показано, что чувство сытости значительно выше на фоне рациона с 60% белка, чем после приема пищи с 19% белка [20].…”
Section: применение при ожиренииunclassified
“…Известно, что чувство голода формируется в результате взаимодействия двух групп веществ: анорексигенов, подавляющих аппетит, и орексигенов, оказывающих противоположный эффект. Основными анорексигенами являются холецистокинин (CCK), глюкагоноподобный пептид 1 (GLP-1), пептид YY (PYY) и лептин; среди орексигенов важную роль отводят грелину [19,21]. Предполагают, что потребление белка контролирует аппетит посредством влияния на выработку ан-и орексигенов.…”
Section: применение при ожиренииunclassified